Light-dependent variations in fatty acid profiles and gene expression in Antarctic microalgal cultures - Jacqui Stuart; Kirsty F. Smith; Matt Miller; John K. Pearman; Natalie Robinson; Lesley Rhodes; Lucy Thompson; Sarah Challenger; Nicole Parnell; Ken G. Ryan (PLoS ONE, 2025)
Photosynthetic eukaryotic microalgae are key primary producers in the Antarctic sea ice environment. Anticipated changes in sea ice thickness and snow load due to climate change may cause substantial shifts in available light to these ice-associated organisms. This study used a laboratory-based experiment to investigate how light levels, simulating different sea ice and snow thicknesses, affect fatty acid (FA) composition in two ice associated microalgae species, the pennate diatom Nitzschia cf. biundulata and the dinoflagellate Polarella glacialis. FA profiling and transcriptomic analyses were used to compare the impact of three light levels: High (baseline culturing conditions 90 ± 1 μmol photons m−2 s−1), mid (10 ± 1 μmol photons m−2 s−1); and low (1.5 ± 1 μmol photons m−2 s−1) on each isolate. Both microalgal isolates had altered growth rates and shifts in FA composition under different light conditions. Nitzschia cf. biundulata exhibited significant changes in specific saturated and monounsaturated FAs, with a notable increase in energy storage-related FAs under conditions emulating thinner ice or reduced snow cover. Polarella glacialis significantly increased production of polyunsaturated FAs (PUFAs) in mid light conditions, particularly octadecapentaenoic acid (C18:5N-3), indicating enhanced membrane fluidity and synthesis of longer-chain PUFAs. Notably, C18:5N-3 has been identified as an ichthyotoxic molecule, with fish mortalities associated with other high producing marine taxa. High light levels caused down regulation of photosynthetic genes in N. cf. biundulata isolates and up-regulation in P. glacialis isolates. This and the FA composition changes show the variability of acclimation strategies for different taxonomic groups, providing insights into the responses of microalgae to light stress. This variability could impact polar food webs under climate change, particularly through changes in macronutrient availability to higher trophic levels due to species specific acclimation responses. Further research on the broader microalgal community is needed to clarify the extent of these effects.